2009
DOI: 10.1093/jxb/erp107
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dwarfing genes on seedling root growth of wheat

Abstract: Most modern wheat cultivars contain major dwarfing genes, but their effects on root growth are unclear. Nearisogenic lines (NILs) containing Rht-B1b, Rht-D1b, Rht-B1c, Rht8c, Rht-D1c, and Rht12 were used to characterize the effects of semi-dwarfing and dwarfing alleles on root growth of 'Mercia' and 'Maris Widgeon' wheat cultivars. Wheat seedlings were grown in gel chambers, soil-filled columns, and in the field. Roots were extracted and length and dry mass measured. No significant differences in root length w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 40 publications
10
117
1
Order By: Relevance
“…The panel included two sets of isogenic lines to test the effect of Rht alleles on root activity, as the literature is not clear on how different Rht alleles affect root growth and depth (e.g. Wojciechowski et al 2009;Miralles et al 1997). We compared the tall RhtC (RhtB1a) and dwarf Rht3 (Rht-B1c) near isogenic lines, allelic at the Rht-B1 locus, in a Mercia background.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The panel included two sets of isogenic lines to test the effect of Rht alleles on root activity, as the literature is not clear on how different Rht alleles affect root growth and depth (e.g. Wojciechowski et al 2009;Miralles et al 1997). We compared the tall RhtC (RhtB1a) and dwarf Rht3 (Rht-B1c) near isogenic lines, allelic at the Rht-B1 locus, in a Mercia background.…”
Section: Plant Materialsmentioning
confidence: 99%
“…As discussed above, this can be problematic. For example, Wojciechowski et al (2009) showed that the effect of Rht genes on root growth was strongly positive in gel cultures but strongly negative in soil. Potential approaches for efficient phenotyping of root traits under controlled conditions have recently been reviewed by Gregory et al (2009), who indicated significant emerging capability.…”
Section: Lessons From Individual Root Traits For Water Capturementioning
confidence: 99%
“…Root characters affect plant establishment, water and nutrient uptake in the field, especially in water limited regions. The effects of GAI Rht genes on wheat root system varied in previous studies, as little or only a slightly negative effect [35,36] and strong negative effects observed in semi dwarf wheat cultivars with GAI dwarfing genes RhtB1b and Rht-D1b [37,38]. Most works on GAR dwarfing genes indicated that less negative effects were observed on wheat root system [22].…”
Section: Discussionmentioning
confidence: 99%